Theoretical foundation of the scientific-investigative training process of the clinical researcher - Tatiana Marañon Cardonne; Pedro Oropesa Roblejo; Llilian Dangelis Vaillant Lora; Zulien Mercedes Cárdenas Godefoy; Kenia Mastrapa Cantillo (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
The scientific-investigative training of the clinical researcher is in correspondence with the methodology for conducting clinical trials from the dynamics generated and its relationship with current social demands. The objective of the work was to theoretically base the scientific-investigative training of the clinical researcher.